The analysis of kinematic rolling pairs such as «cylinder in cylinder» - A. Kh. Shamutdinov; I. Yu. Lesnyak (Омский научный вестник)
The article is devoted to the study of specific kinematic pairs used in many areas of mechanical engineering: the so-called «rolling pairs» used in many mechanisms. The study is based on a detailed study of the structure of the «cylinder in cylinder» connection, and their geometric parameters are considered. The analysis is considered by the location of the axes of the cylinders between themselves: when the axes are parallel and when they intersect or intersect at an angle of 90 º. This study complements the data in the theory of description of kinematic pairs, in particular, rolling pairs, and makes it possible to synthesize their new types for their rational use in the mechanisms of many industries.